A Cost Analysis of Systematic Vitamin D Supplementation in the Elderly Versus Supplementation Based on Assessed Requirements - Ericson Lisa; Hovstadius Bo; Carlsson Martin; Petersson Göran; Wanby Pär (Journal of Aging Research And Healthcare, 2017)
Hypovitaminosis D is common among older people and treatment with vitamin D is associated with reduced risk of falls and fractures. This paper provides a cost analysis of assessing the vitamin D status of and providing the pharmaceuticals for elderly citizens in Kalmar County, Sweden (population approximately 230,000). Four hypothetical interventions were analyzed: (a) systematic vitamin D/calcium supplementation to all elderly (≥75 years), (b) assessment of vitamin D status in elderly and supplementation to those with insufficient levels, (c) systematic vitamin D/calcium supplementation to all nursing-home residents, and (d) assessment of vitamin D status in nursing-home residents and supplementation to those with insufficient levels. The calculations were based on an estimated reduction in overall costs due to the assessed number of hip fractures after vitamin D/calcium supplementation. The annual net economic benefit of vitamin D/calcium supplementation was estimated at (a) €304,000, (b) €860,000, (c) €755,000, and (d) €740,000. The provision of systematic vitamin D supplementation to nursing-home residents would provide a substantial net economic benefit to society and assessment of the vitamin D status before starting supplementation does not seem to be necessary. Although assessment of all elderly citizens would be more comprehensive, the true proportion with insufficient vitamin D levels in the general population is uncertain and to reaching consensus on the most advantageous daily vitamin D intake, vitamin D blood levels are necessary. Also, systematic supplementation to all elderly would result in other outcomes that could be worth the cost, but that remains to be evaluated.
Keywords: Vitamin D